(untitled) (Herald of the National Children’s Medical Center, 2025)
Background. To study the role of Echocardiography in young children with congenital heart defects in different levels of medical care. Materials and methods. Taking into account the regional and territorial features and the organizational structure of medical care in the Republic of Uzbekistan, the diagnostic stages were identified, which consist of 3 levels: district, regional and republican. To visually provide data, children with moderate and mild congenital heart defects according to the J. I. Hoffman classification [4] were excluded from the study and children with severe cenotic CHD, such as transposition of the main vessels (D-TGA) and tetralogy of Fallot with pulmonary atresia (TOF with PA), were selected. As we know, the diagnosis of these types of CHD is more accessible at all levels of medical care. The medical history of 46 young children with congenital heart defects (CHD) who were hospitalized at the National Children’s Medical Center for surgical intervention to correct severe heart defects in the period from 2021 to 2022 was studied. Results. Of the total sample of patients with CHD, the diagnosis of transposition of great arteries (TGA) was confirmed in 43.5% of children, and the diagnosis of TOF with LA atresia was confirmed in 56.5% of children. Of the total number of children with CHD, female accounted for 39.1%, and male -60.9%. Among children with TMS, female accounted for 55%, male -45%, and among children with TOF, female accounted for 26.9%, male -73.1%. These data indicate that in our study, CHD, in particular TOF with PA, are more common in male, while TGA is more often diagnosed in female. An analysis of the obtained data from various region and levels on the correspondence of CHD diagnoses with the last level of medical care showed that in the region levels 43.7% of cases were accurately diagnosed with CHD, including diagnostic coincidences of TGA in 45.0% of cases, and TOF with PA in 42.3% of cases. The data obtained from the regional level on the correspondence of CHD diagnoses with the last level of medical care showed that in the regional level 69.6% of cases were accurately diagnosed with CHD, including diagnostic coincidences of TGA in 69.2% of cases, and TOF with PA in 70.0% of cases. The results of the last-stage echocardiographic diagnosis showed that in 95.6% of cases, an accurate diagnosis of CHD was performed, including diagnostic coincidences of TGA in 95.0% of cases, and OTF with PA atresia in 96.2% of cases, these data were compared with diagnoses after surgery. Conclusion. Given the discrepancies in diagnoses at different stages of medical care, there is a need to create a system for assessing the level of knowledge of cardiologists and specialists involved in ultrasound diagnosis of congenital heart defects, especially at the first stage of medical care. On the basis of republican cardiological centers or institutions with facilities for providing cardiological and cardiac surgery, it is necessary to create permanent advisory commissions working in real time, and these commissions will resolve controversial issues related to the diagnosis of CHD at the first and second stages of medical care, using modern global network capabilities.